A Multivariate Framework for MSME Financial Performance: Financial and Strategic Determinants in Developing Island Economies - BATE'E, Maria Magdalena; FACHRUDIN, Khaira Amalia; SYAHYUNAN, Syahyunan; SILALAHI, Amlys Syahputra (Theoretical and Practical Research in Economic Fields, 2025)
This study aims to identify the financial and strategic determinants affecting the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in developing island economies. It specifically explores the roles of financial inclusion and internal capabilities such as financial literacy, financial culture, innovation, and strategic orientation. A quantitative approach using Structural Equation Modeling - Partial Least Squares (SEM-PLS) was adopted. Data were collected from 210 MSMEs operating in the Nias Islands, Indonesia. The model examines relationships among latent constructs, including financial literacy, inclusion, innovation, strategic orientation, financial culture, access to finance, and financial performance. The study is limited to a geographically specific setting (Nias Islands) and uses a cross-sectional design. Caution is advised in generalizing the results beyond similar contexts. Future research should consider longitudinal and qualitative methods to explore causal depth. This study contributes to theory by extending the Resource-Based View (RBV) to include contextual factors such as culture and geography. The proposed multivariate framework offers a replicable model for analyzing MSME financial performance in financial and infrastructurally constrained environments. The findings reveal that access to finance significantly mediates the relationship between internal capabilities (financial literacy, innovation, and strategic orientation) and MSME financial performance. Meanwhile, financial inclusion and financial culture influence performance only through access to finance. Innovation and strategic orientation also have direct effects on performance. The multivariate model demonstrates strong explanatory power, with R² = 0.73 for financial performance.